2017
DOI: 10.1103/physreve.95.062144
|View full text |Cite
|
Sign up to set email alerts
|

When memory pays: Discord in hidden Markov models

Abstract: When is keeping a memory of observations worthwhile? We use hidden Markov models to look at phase transitions that emerge when comparing state estimates in systems with discrete states and noisy observations. We infer the underlying state of the hidden Markov models from the observations in two ways: through naive observations, which take into account only the current observation, and through Bayesian filtering, which takes the history of observations into account. Defining a discord order parameter to disting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The trade-offs between the two, captured by the Pareto front, have the structure of a first-order phase transition with phase-coexistence protocols interpolating between the two phases. Such a phase transition may be a common feature of optimization problems: they occur in optimal complex networks [57,58], statistical in-ference [59]; and similar phenomena were observed in a quantum control problem with varying constraints [60] and in the utilization of memory in an information engine [61][62][63]. Finally, we observed that the minimum work fluctuation and the phase coexistence protocols do not become quasistatic even for very long protocols and are thus not accessible by a linear theory.…”
supporting
confidence: 58%
“…The trade-offs between the two, captured by the Pareto front, have the structure of a first-order phase transition with phase-coexistence protocols interpolating between the two phases. Such a phase transition may be a common feature of optimization problems: they occur in optimal complex networks [57,58], statistical in-ference [59]; and similar phenomena were observed in a quantum control problem with varying constraints [60] and in the utilization of memory in an information engine [61][62][63]. Finally, we observed that the minimum work fluctuation and the phase coexistence protocols do not become quasistatic even for very long protocols and are thus not accessible by a linear theory.…”
supporting
confidence: 58%
“…For example, the entropy of a binary HMM was calculated [26] by a mapping to a one-dimensional Ising model. Lathouwers and Bechhoefer have investigated [27] transitions with respect to whether the reconstruction of a hidden sequence is possible or not depending on whether data can be kept in memory. Allahverdyan and Galastyan have investigated [28,29] the maximum a posteriori (Viterbi) sequence as a function of a noise parameter and found transitions between regions where almost full sequence reconstruction is possible and regions where not.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress within the emerging field of stochastic thermodynamics has led to a deeper understanding of the relationship between information and entropy at mesoscopic scales, leading to e.g., the refinement of the second law of thermodynamics for systems with feedback control [7]. These works study fundamental thermodynamic bounds governing processes that convert information into work and/or heat, and vice versa, both in theory [5,[8][9][10][11][12][13][14][15][16][17][18][19], and experiment [20][21][22][23][24][25][26][27][28].…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%